Literature Review: The relationship of the physical quality of the environment in the dwelling to the incidence of Acute Respiratory Infection (ARI) - Rismaya Fika Nur Aryanti (Universitas Airlangga, 2021)
Background: Acute Respiratory Infection (ARI) is a disease transmitted by viruses. This health problem persists from year to year, starting from developing countries to developed countries there are still morbidity and mortality rates due to ARI. One of the factors that can affect human health is environmental factors which include occupancy density, ventilation area, natural lighting, humidity, temperature, conditions and types of walls, and floors.Purpose: This literature study aims to analyze the relationship between the physical quality of the occupancy and the occurrence of acute respiratory infections (ARI).Reviews: The results of the journal search were found as many as 17 journals that met the inclusion criteria set by the researcher. Most of the research found used a cross sectional study design, but some studies also used case control and cohort study designs. Several different results were found for each study, but still showed similarities, namely the incidence of ARI in each study.Conclusion: The journal review that has been conducted can conclude that there is a relationship between the area of ventilation, humidity, temperature, natural lighting, occupancy density, conditions and types of walls, as well as conditions and types of floors. There are differences from each of the research results, but there are still similarities which state that there is a relationship between the physical quality of the environment at home and the incidence of ARI.